2016
DOI: 10.1016/j.cmet.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Biology of Glucagon-like Peptide-1

Abstract: Glucagon-like peptide-1, produced predominantly in enteroendocrine cells, controls glucose metabolism and energy homeostasis through regulation of islet hormone secretion, gastrointestinal motility, and food intake, enabling development of GLP-1 receptor (GLP-1R) agonists for the treatment of diabetes and obesity. GLP-1 also acts on the immune system to suppress inflammation, and GLP-1R signaling in multiple tissues impacts cardiovascular function in health and disease. Here we review how GLP-1 and clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
386
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(403 citation statements)
references
References 131 publications
(192 reference statements)
7
386
2
8
Order By: Relevance
“…In addition, GLP-1 RAs reduce blood pressure during chronic treatment and increase pulse rate, both by still unknown mechanisms. The agonists also appear to reduce postprandial triglyceride concentrations (8)(9)(10) by an effect that appears to be independent of the effects on gastric emptying, but may reflect inhibition of chylomicron formation (11). Agonist treatment does not lead to fat malabsorption, though.…”
mentioning
confidence: 99%
“…In addition, GLP-1 RAs reduce blood pressure during chronic treatment and increase pulse rate, both by still unknown mechanisms. The agonists also appear to reduce postprandial triglyceride concentrations (8)(9)(10) by an effect that appears to be independent of the effects on gastric emptying, but may reflect inhibition of chylomicron formation (11). Agonist treatment does not lead to fat malabsorption, though.…”
mentioning
confidence: 99%
“…Indeed, several randomized controlled clinical trials have demonstrated significant clinical improvement in human subjects with Parkinson's disease (93). Despite the appeal of current GLP-1R agonists for the treatment of T2D, market penetration for many GLP-1R agonists remains disappointing, raising questions about the potential clinical classes used for treatment of T2D, the GLP-1R agonists and SGLT-2 inhibitors, produce weight loss, effective reduction of A1c, a low incidence of hypoglycemia, and reductions in rates of major adverse cardiovascular events and cardiovascular death (75,87).…”
Section: Glps: Current Use and Future Considerationsmentioning
confidence: 99%
“…Native GLP-1 increases flow-mediated vasodilation, enhances heart rate (HR) and cardiac output, and is cardioprotective in preclinical studies, most notably in animals with ischemic cardiac injury (78). Although degradationresistant GLP-1R agonists have minimal effects on blood vessels (79), they increase HR and reduce cardiac inflammation and infarct size in animals with experimental myocardial infarction (75,80). Understanding the mechanisms through which GLP-1 exerts cardioprotection is challenging, since the GLP-1R is largely expressed in atrial and not ventricular cardiomyocytes (81).…”
Section: Challenges In Studies Of Glp-1 and In Development Of Glp-1r mentioning
confidence: 99%
“…GLP-1 is a hormone released from the gut in response to food intake and acts on GLP-1R to stimulate glucose-dependent insulin secretion from pancreatic Ī² cells, reduce glucagon secretion from pancreatic Ī± cells, as well as decrease gastric motility and appetite 1 . Given its physiological effects, GLP-1R represents an important drug target for type-2 diabetes and obesity 2 , with GLP-1 and its analogs already serving as approved therapeutics.…”
mentioning
confidence: 99%